Challenges in macroscopic measurement of diffusion in zeolites - Brandani, Stefano (Diffusion Fundamentals, 2007)
The paper presents a brief historical overview of the field of the measurement of diffusion in zeolites. The focus will be on macroscopic measurements, i.e. when diffusion through entire crystals is studied. While this may appear to be a simple task, we will see that there are difficulties in obtaining reliable results. Two case studies, the volumetric/piezometric experiment and the Transient Analysis of Products (TAP) apparatus are discussed and ways to improve either the experiments or the way in which the results are analyzed are presented. The author’s perspective into what are the current challenges in the field concludes the paper.